2023
DOI: 10.1186/s12890-023-02307-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a risk prediction model for prolonged mechanical ventilation after lung transplantation: a retrospective cohort study

Abstract: Background Prolonged mechanical ventilation (PMV), mostly defined as mechanical ventilation > 72 h after lung transplantation with or without tracheostomy, is associated with increased mortality. Nevertheless, the predictive factors of PMV after lung transplant remain unclear. The present study aimed to develop a novel scoring system to identify PMV after lung transplantation. Methods A total of 141 patients who underwent lung transplantation we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…As the Naive Bayes model provides a good AUC and CA, we then constructed a nomogram plot to predict pancreas rejection in SPK transplantation, as shown in Figure 7, based on clinical and laboratory features. This nomogram-based strategy has been used in other types of transplants, e.g., kidney [22], lung [23], and heart [24], as a means to predict transplant-related events. In our model the 10 top features identified using information gain were incorporated, and our endpoint was the ability to identify or generate risk stratification for pancreas rejection in SPK transplantation, and to our knowledge this is one of the first attempts of model-based risk stratification for pancreas rejection.…”
Section: Resultsmentioning
confidence: 99%
“…As the Naive Bayes model provides a good AUC and CA, we then constructed a nomogram plot to predict pancreas rejection in SPK transplantation, as shown in Figure 7, based on clinical and laboratory features. This nomogram-based strategy has been used in other types of transplants, e.g., kidney [22], lung [23], and heart [24], as a means to predict transplant-related events. In our model the 10 top features identified using information gain were incorporated, and our endpoint was the ability to identify or generate risk stratification for pancreas rejection in SPK transplantation, and to our knowledge this is one of the first attempts of model-based risk stratification for pancreas rejection.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of PMV in in-patients using ECMO as a bridge to LTx was 21.8% in the present study. Gao et al reported that the incidence of PMV (defined as > 72 h) was 31.9%, excluding ECMO-supportive patients 10 . Since PMV is not clearly defined in the literature, the PMV in this study was defined according to the previous large-scale retrospective study, where the mean ventilation time of LTx patients was 5 days 11 .…”
Section: Discussionmentioning
confidence: 99%
“…EVLP lung patients require a ventilator for a long time, spending more time in the ICU. In addition to lengthy hospital and ICU stays, long-term mechanical ventilation (PMV) was linked to worse outcomes after LTx [47]. It was reported that 14% of 690 LTx patients who participated in a single-centre study between 2005 and 2012 suffered long-term mechanical ventilation for more than 21 days [48], where the patient outcomes who lived to be discharged were unaffected.…”
Section: Discussionmentioning
confidence: 99%